Pengaruh Kompensasi, Motivasi Kerja Dan Perilaku Organisasi Terhadap Kinerja Karyawan (Studi di PT. Hagis Mitra Sejahtera Samarinda) - Nuri Antin Rahmadila; Abdul Kodir Djaelani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
This study is used to determine how the effect of compensation and work motivation on employee performance partially at PT. Hagis Mitra Sejahtera Samarinda in this study using 3 variables, namely compensation variable, work motivation is the independent variable and employee performance which is the dependent variable. collected through a questionnaire using a Likert scale and analysis of the data used is multiple linear regression tested using SPSS. Stamp data retrieval using the Slovin formula with an error scale of 0.5 that is to obtain as many as 60 respondents. The results show that compensation has a positive effect on employee performance, work motivation has a positive effect on employee performance and behavior has a negative and insignificant effect on employee performance. Keywords : Compensation, Work Motivation, Organizational Behavior, Employee Performance